2013
DOI: 10.4172/2157-7536.1000139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Testosterone Exposure on Sexually Dimorphic Gene Expression in the Neonatal Mouse Cortex and Hippocampus

Abstract: Objective Using gene expression microarrays and reverse transcription with quantitative polymerase chain reaction (RT-qPCR), we have recently identified several novel genes that are differentially expressed in the neonatal male versus female mouse cortex/hippocampus (Armoskus et al.). Since perinatal testosterone (T) secreted by the developing testes masculinizes cortical and hippocampal structures and the behaviors regulated by these brain regions, we hypothesized that sexually dimorphic expression of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 86 publications
(85 reference statements)
1
6
0
Order By: Relevance
“…Using RT‐qPCR, we confirmed the sex differences in mRNA levels of Ddx3y , Eif2s3x , and Eif2s3y in the neonatal cortex/hippocampus (Armoskus et al, 2014), and found that their expression is independent of prenatal testosterone levels (Armoskus et al, 2014a). In this study, we continued to profile the expression of the other 10 candidates in the developing mouse cortex/hippocampus using RT‐qPCR.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Using RT‐qPCR, we confirmed the sex differences in mRNA levels of Ddx3y , Eif2s3x , and Eif2s3y in the neonatal cortex/hippocampus (Armoskus et al, 2014), and found that their expression is independent of prenatal testosterone levels (Armoskus et al, 2014a). In this study, we continued to profile the expression of the other 10 candidates in the developing mouse cortex/hippocampus using RT‐qPCR.…”
Section: Resultssupporting
confidence: 60%
“…To examine if sexually dimorphic expression of selected genes was regulated by prenatal androgens, pregnant mice received a subcutaneous injection of either vehicle (0.05 ml sesame oil) or testosterone propionate (TP, 100 μg in 0.05 ml; Sigma‐Aldrich) daily beginning on E16 (16 days after a mating plug was seen) until PN0 as described previously (Armoskus et al, 2014a). This treatment was to mimic the testosterone surge observed in male embryos during late gestation.…”
Section: Methodsmentioning
confidence: 99%
“…To determine if the Arctic model has sex-specific effects, we used edgeR (30) to identify differentially expressed genes between male and female Arc mice. Genes up-regulated in females were mainly those known to be sexually dysmorphic genes (35), such as Xist and Tsix, which are located on the X-chromosome, whereas males presented upregulation of genes known to be male-specific, such as Eif2s3y and Ddx3y, which are located on the Y-Chromosome ( Figures S4A-B ). Therefore, differential expression analyses showed lack of sex-specific changes in the hippocampus and cortex of Arc mice at all ages.…”
Section: Resultsmentioning
confidence: 99%
“…route, were continued in pups on alternate days from P1 to P7. Together, the objective of the prenatal and postnatal androgenization periods was to recapitulate the perinatal androgen surge and defeminize female mice as described (26,27). Because perinatal hormone treatment can alter adult hormone profiles by influencing the hypothalamic−pituitary−gonadal axis, perinatally androgenized male and female mice, along with their SO-treated counterparts, were GDX in adulthood prior to use in experiments to remove this confounding effect (25).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we hypothesized that perinatal androgens in males were critical to development of sexually dimorphic anaphylaxis responses. To test this hypothesis, we inhibited perinatal androgen production in males by exposing pregnant dams to low and high doses of di-(2-ethylhexyl) phthalate (DEHP), a pervasive environmental endocrine disruptor that has well-established antiandrogen effects although it decreases testosterone production in Leydig cells of the testes (26,27). Administration of DEHP to dams was continued postpartum (postnatal d0 to d7), resulting in lactational exposure and thus also inhibiting the postnatal androgen surge in male offspring (Fig.…”
Section: Perinatal Androgens In Males As Critical Early-life Modulatomentioning
confidence: 99%